2006
DOI: 10.1002/mds.21135
|View full text |Cite
|
Sign up to set email alerts
|

New syndromic form of benign hereditary chorea is associated with a deletion of TITF‐1 and PAX‐9 contiguous genes

Abstract: Benign hereditary chorea is a rare autosomal dominant disorder presenting with a childhood-onset and slowly progressive chorea. The objective of this study was to describe the clinical and genetic features of 3 patients who developed childhood-onset chorea. Three affected patients from three generations of a family with benign hereditary chorea associated with a multisystemic disorder of the basal ganglia, thyroid, lungs, salivary glands, bowels, and teeth. The TITF-1 gene was screened by microsatellite analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 15 publications
2
52
0
4
Order By: Relevance
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Спектр легочных расстройств включает в себя респираторный дистресс-синдром новорожденных, рецидивирующие инфекции, острый респираторный дистресс-синдром, бронхиальную астму, фиброз легких, интерстициальные заболевания легких (ИЗЛ) [19,20]. Синдром МЛЩЖ относится к ИЗЛ, встречающимся пре-имущественно у младенцев, согласно классификации Американского торакального сообщества, представлен-ной в руководстве по детским ИЗЛ у младенцев (2013), к группе заболеваний, ассоциированных с нарушением синтеза сурфактанта [21,22].…”
Section: клиническая характеристика и диагностикаunclassified
“…В других сериях наблюдений сообща-лось о мутациях NKX2-1 с полной триадой синдрома МЛЩЖ в 36-50% случаев, с поражением головного моз-га и щитовидной железы -в 30-32%, изолированными неврологическими нарушениями -в 10-13% [10,12]. У пациентов с мутацией гена NKX2-1 также обнару-живаются дисморфические черты лица и черепа, такие как гипертелоризм, микрогнатия, высокое дугообразное небо, выдающийся лоб, луковичный кончик носа, олиго-донтия [12,[19][20][21]. В табл.…”
Section: клиническая характеристика и диагностикаunclassified
See 2 more Smart Citations